INTERAÇÃO INTERESPECÍFICA ENTRE O PARASITOIDE TELENOMUS REMUS NIXON (HYMENOPTERA: SCELIONIDAE) E O PREDADOR DORU LUTEIPES SCUDDER (DERMAPTERA: FORFICULIDAE) SOBRE OVOS DE SPODOPTERA FRUGIPERDA (J.E. SMITH) (LEPIDOPTERA: NOCTUIDAE) - Carneiro, T.r.; Fernandes, O.a. [UNESP] (Instituto Biológico, 2020)
This work aimed at evaluating the interaction between Telenomus remus andD. luteipes. S. frugiperda eggs previously parasitized by T. remus were offered to D. luteipes and D. luteipes eggs were offered to T. remus. To study the influence of different embryonic development stages of the parasitoid, we offered S. frugiperda previously parasitized eggs at different embryonic development stages to the predator. And we offered predator eggs at different embryonic development stages to the parasitoid. The behavior of insects was observed. When S. frugiperda eggs were exposed to T. remus previously, D. luteipes eat the eggs until three days after parasitism. T. remus parasitized D. luteipes eggs until 48h they were laid, but only when predator females were absent.

Este trabalho teve por objetivo verificar a interação entre o parasitoide Telenomus remus e o predador Doru luteipes. Para tanto, posturas deS. frugiperda parasitadas porT. remus foram ofertadas a D. luteipes e ovos de D. luteipes foram ofertados a T. remus. Essa oferta levou em consideração diferentes fases do desenvolvimento embrionário do parasitoide e do predador. Constatou-se que quando as posturas de S. frugiperda foram expostas primariamente a T. remus. D. luteipes as consumiu, mas somente até o terceiro dia após o parasitismo.T. remus parasitou ovos deD. luteipes com até 48h de desenvolvimento embrionário, mas apenas quando as fêmeas do predador estavam ausentes. Diante disso, a interação intraguilda parece não ser um fator importante de regulação populacional destas espécies.
INTERACTION BETWEEN TELENOMUS REMUS NIXON (HYMENOPTERA: SCELIONIDAE) AND DORU LUTEIPES SCUDDER (DERMAPTERA: FORFICULIDAE) ON SPODOPTERA FRUGIPERDA (J.E. SMITH) (LEPIDOPTERA: NOCTUIDAE) EGGS
Keywords: Behavior; biological control; intraguild competition; natural enemies; predation; Competição intraguilda; controle biológico; inimigos naturais; comportamento; predação